Evaluation of Air and Noise Pollution and Behavioural Effects on Exposed School Children: Case Study in Kampar, Malaysia - Foong, Jun Ming (2015)
In recent decades, there have been abundant time series studies that suggested the air and noise pollution was associated with poor academic performance of students. Therefore, Kampar town has been selected as study area to evaluate the air and noise pollution level around school areas, and to determine the behavioural effects on the exposed school children. In this study, air and noise monitoring together with survey research were done to discover the findings. The results showed that the average concentrations of sulphur dioxide (SO2) were not in compliance to the Malaysian Ambient Air Quality Guidelines (MAAQG); while the other air pollutants such as carbon monoxide (CO), nitrogen dioxide (NO2) and ground – level ozone (O3) were all well below the guidelines. The average noise levels of the selected schools have also exceeded the 50 dB (A) daytime limit from time to time as indicated by Department of Environment (DOE). On top of that, the majority of students have expressed that annoyance and stress were the main negative behavioural effects as a result of air and noise pollution.